A combined immunopeptidomics, proteomics, and cell surface proteomics approach to identify immunotherapy targets for diffuse intrinsic pontine glioma - Pandey, Kirti; Wang, Stacie S.; Mifsud, Nicole A.; Faridi, Pouya; Davenport, Alexander J.; Webb, Andrew I.; Sandow, Jarrod J.; Ayala, Rochelle; Monje, Michelle; Cross, Ryan S.; Ramarathinam, Sri H.; Jenkins, Misty R.; et al. (Frontiers in Oncology, 2023)
Diffuse intrinsic pontine glioma (DIPG), recently reclassified as a subtype of diffuse midline glioma (DMG), is a highly aggressive brainstem tumour affecting children and young adults, with no cure and a median survival of only 9 months. Conventional treatments are ineffective, highlighting the need for alternative therapeutic strategies such as cellular immunotherapy.However, identifying unique and tumor-specific cell surface antigens to target with chimeric antigen receptor (CAR) or T cell receptor (TCR) therapies is challenging.In this study, a multi-omics approach was used to interrogate patient-derived DIPG cell lines and identify potential targets for immunotherapy. Through immunopeptidomics, a range of targetable peptide antigens from cancer testis and tumour-associated antigens, as well as peptides derived from human endogenous retroviral elements were identified. Proteomics analysis also revealed upregulation of potential drug targets and cell surface proteins such as CD276 (B7H3), IL-13R2, HER2, EphA2 and EphA3. The results of this study provide a valuable resource for the scientific community to accelerate immunotherapeutic approaches for DIPG. Identifying potential targets for CAR and TCR therapies could open up new avenues for treating this devastating disease.